RCP para proveedores de salud - Gulli, Benjamín; Piazza, Gina; Rahmn J., Stephe (Editorial Jones & Bartlett, 2012)
RCP Para Proveedores de Salud, Cuarta Edicion is the Spanish Edition of the Emergency Care & Safety Institute's Health Care Provider CPR, Fourth Edition training program. Based on the 2010 International Consensus Guidelines for Cardiopulmonary Resuscitation (CPR) and Emergency Cardiac Care (ECC), RCP Para Proveedores de Salud, Cuarta Edicion is ideal for use within courses designed to certify health care providers in CPR and AED. More than a stand-alone text, this student manual is the center of an integrated teaching and learning system that offers many resources to better support instructors and prepare students. This manual includes: Coverage of the 2010 CPR and ECC Guidelines: Clear, concise direction on how to perform CPR and use an AED during an emergency. Skill Drills: Offer step-by-step explanations and visual summaries of important skills. Emergency Care Wrap-Up Tables: Provide a concise summary of what signs first aiders should look for and what treatment steps they should take. To order these titles in Mexico, please call 01 800 134 6720. To order in Central and South America, please contact Intersistemus at 011800 134 6720 or visit: www.rcp-dinsamex.com.mx.